2022
DOI: 10.1126/sciadv.abj3995
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cellular close-ended tunneling nanotubes through mechanical deformation

Abstract: Membrane nanotubes or tunneling nanotubes (TNTs) that connect cells have been recognized as a previously unidentified pathway for intercellular transport between distant cells. However, it is unknown how this delicate structure, which extends over tens of micrometers and remains robust for hours, is formed. Here, we found that a TNT develops from a double filopodial bridge (DFB) created by the physical contact of two filopodia through helical deformation of the DFB. The transition of a DFB to a close-ended TNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Furthermore, we observed that cells forming TNTs use other pre-existing protrusions as guides to grow (Movie S7 &8), the lack of N-Cadherin would therefore cause the disappearance of these guides and therefore these iTNTs would have no reference for growth/retraction. Our data are supported by recent findings showing that double filopodial bridges (DFB, that the authors consider as precursors of close-ended TNTs in HeLa cells), were dissociated resulting into separation of paired cells by downregulating N-Cadherin (or inhibiting its function with EGTA) (38). In the same study, the authors show N-Cadherin decorating the whole DFB/TNT-like structure and preferentially enriched in the areas of contact with opposite cells.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we observed that cells forming TNTs use other pre-existing protrusions as guides to grow (Movie S7 &8), the lack of N-Cadherin would therefore cause the disappearance of these guides and therefore these iTNTs would have no reference for growth/retraction. Our data are supported by recent findings showing that double filopodial bridges (DFB, that the authors consider as precursors of close-ended TNTs in HeLa cells), were dissociated resulting into separation of paired cells by downregulating N-Cadherin (or inhibiting its function with EGTA) (38). In the same study, the authors show N-Cadherin decorating the whole DFB/TNT-like structure and preferentially enriched in the areas of contact with opposite cells.…”
Section: Discussionsupporting
confidence: 90%
“…The cytoskeleton of TNTs in HEK293 cells is composed of F-actin without microtubules and vimentin ( Supplementary Figure S3A ). It has been shown that cadherin adhesion molecules are present at the tip of TNTs or between thin TNTs ( Jansens et al, 2017 ; Sartori-Rupp et al, 2019 ; Chang et al, 2022 ). Here, we show that HEK293 cells expressed N-cadherin but not E-cadherin at cellular junctions ( Supplementary Figure S3B ).…”
Section: Resultsmentioning
confidence: 99%
“…It is close to the lateral force (approx. 40 pN/μm) that is needed to bend TNTs between Hela cells using optical tweezers ( Chang et al, 2022 ). Moreover, both studies revealed no threshold was required for bending TNTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1177 proteins were identified in at least 9 preparations (table S1). We first observed that proteins previously described in TNTs, like actin, Myosin10 [36], ERp29 [30], or N-cadherin [2, 37] were indeed present in TNTome. Less than 100 nuclear proteins, i.e.…”
Section: Resultsmentioning
confidence: 99%